Priporočila za obravnavo bolnikov s kožnim melanomom - Marko Hočevar; Primož Strojan; Janja Ocvirk; Martina Reberšek; Marko Boc; Barbara Perić; Boštjan Luzar; Jože Pižem; Olga Blatnik; Katarina Karner; Tomi Bremec; Tanja Ručigaj Planinšek (Onkologija, 2018)
ni abstrakta